Gender quotas on boards of directors - Nina Smith (IZA World of Labor, 2018)
Arguments for increasing gender diversity on boards of directors by gender quotas range from ensuring equal opportunity to improving firm performance. The introduction of gender quotas in a number of countries has increased female representation on boards. Current research does not justify gender quotas on grounds of economic efficiency. In many countries the number of women in top executive positions is limited, and it is not clear from the evidence that quotas lead to a larger pool of female top executives, who are the main pipeline for boards of directors. Thus, other supplementary policies may be necessary if politicians want to increase the number of women in senior management positions.
Keywords: G34; J16; L25; 330; gender quotas; boards of directors; firm performance